Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages The Education of the Medical Student in Practical Obstetrics. To errors in judgment in practice or treatment by doctors or midwives the Maternal Mortality Committee trace another 17 per cent. of the deaths. Sir George Newman states that action was promptly taken on the Committee's recommendations, which were sent by the Minister of Health to the Lord President of the Privy Council and by him transmitted to the General Medical Council. The question received the immediate consideration of the General Medical Council and is now being dealt with by the licensings bodies. Unfortunately some time must elapse before we can hope to see the results of improved training on the new generation of medical students. Meanwhile we must encourage every step that can be taken to deal with the situation by the existing powers. The Medical Officer for Northumberland, dealing with the need for the training of students of the next generation "to examine and supervise the health of the patient prior to delivery, with the idea of prevention rather than cure," comments on the considerable amount of education needed both for medical men and mothers. The Medical Officer for Finsbury, who notifies a maternal mortality rate of 8.47 which has sprung up, we believe, owing to exceptional circumstances unlikely to recur, from a rate of 2 or 3 per 1000 in several previous years, analyses the cases in what amounts to a terrible indictment. In this the poverty of the home, the lack of transport, the lack of hospital accommodation and the ignorance of the doctor all play their part. He supports the recommendation that "an experienced midwife should accompany the medical students to their cases during the period of training to help the student and to hold on to the difficult or complicated cases while expert advice is being sought" and recommends that the services of a consultant should always be available. It is gratifying to learn, as we do, from the Reports from Liverpool and Nottingham, of the co-ordination between ante-natal clinics and doctors and midwives. We note many allusions to the excellent results arising from the appointment of Obstetric Consultants. Several Medical Officers mention that women's lives have been saved. We may give as instances the Report of the Denbigh County Council where of the cases of puerperal sepsis referred to the consultant all "made a good recovery," and the Report from Carmarthen, in which the Medical Officer asks for skilled obstetric specialists for Maternity Homes. A good many Boroughs and Counties have found the appointment of consultants for puerperal sepsis as recommended by the (15) 292/824/1/58